1998
DOI: 10.1046/j.1365-2222.1998.028s5195.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in older people

Abstract: From the clinical perspective, asthma in the older patient may be difficult to diagnose because of the non-specificity of presentation and the wide range of differential diagnoses. Prior to confirmation of asthma in the older patient, both respiratory and cardiac investigation may be necessary. Polypharmacy is inherent in treating older people and accurate drug histories are essential in order to identify patients with drug-induced bronchospasm and avoid interactions with asthma medication. Patient and carer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…1 The diagnosis of asthma in adults can be difficult and confounded by comorbidities. A gold standard test would simplify the diagnosis of asthma and perhaps reduce the frequency of underdiagnosed asthma [2][3][4][5] ; however, no gold standard exists.…”
mentioning
confidence: 99%
“…1 The diagnosis of asthma in adults can be difficult and confounded by comorbidities. A gold standard test would simplify the diagnosis of asthma and perhaps reduce the frequency of underdiagnosed asthma [2][3][4][5] ; however, no gold standard exists.…”
mentioning
confidence: 99%
“…Interest in this field was stimulated by a study carried out by the author in 1986 which showed that 40 percent of community dwelling patients with a mean age of 80 years had a completely inadequate technique with a metered dose inhaler [20]. A number of subsequent surveys demonstrated a similar finding, and the use of less technically demanding devices has been shown to reduce this percentage only moderately, unless a substantial programme of screening and training was undertaken [23][24][25][26][27]. In most studies, the commonest errors in technique have been related to poor coordination between actuation of devices and inhalation; sometimes referred to as hand-lung in-coordination [20,28,29].…”
Section: Typical Errors In Inhaler Techniquementioning
confidence: 91%
“…One important factor, highlighted by the work on spirometry technique and inhaler use, is the importance of a good training programme, sympathetic trainers and technicians and reinforcement. In inhaler research, several studies have demonstrated the substantially higher success rates in inhaler training programmes conducted by trained and dedicated staff [24,27,30]. This applies at all ages and there is some evidence that it is effective in elderly subjects with normal cognitive scores or very slight cognitive impairment.…”
Section: Implications For Inhaler Designmentioning
confidence: 97%
“…Bei älteren Patienten wird die Diagnose eines Asthmas oft nicht gestellt oder übersehen [11], obwohl prinzipiell Menschen jeden Alters neu an einem Asthma erkranken können [12]. Die Wahr− scheinlichkeit der Erstdiagnose Asthma nimmt mit zunehmen− dem Alter ab, und die Wahrscheinlichkeit von Lungenschäden durch Zigarettenrauchen oder Exposition gegenüber anderen in− halierbaren Umweltschadstoffen zu.…”
Section: Asthma Bei äLteren Patientenunclassified
“…3 einander gegenübergestellt.Ältere Patienten weisen häufig episodisch auftretende Atemne− bengeräusche, Atemnot und Husten als Folge einer Insuffizienz des linken Herzens mit Lungenstauung auf. Dieser Beschwerde− komplex wird gelegentlich fälschlich als Asthma cardiale be− zeichnet[11]. Das gleichzeitige Vorhandensein von vermehrten Beschwerden bei körperlicher Anstrengung und nachts kann zur diagnostischen Unsicherheit beitragen.…”
unclassified